OGPU organs and Soviet aviation (1928–1934) - A. S. Stepanov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the analysis of the activities of Soviet special services in the aviation sector during the formation and development of Soviet aviation and related industries. The problems of Soviet aviation, largely determined by the state of society and the economy in the USSR, are characterized on the basis of office documents of the special services and other departments. Using concrete examples, the tasks performed by the OGPU body for operational maintenance of Soviet aviation are considered. The author comes to the conclusion that the materials of the special services, despite the need for critical perception of some of their conclusions, allow us to get an objective idea of the problems of Soviet aviation during its quantitative and qualitative growth (1928–1934).